(untitled) (Journal of Science and Technology, 2016)
A plethora of both cross-country and country-specific studies have been undertaken to estimate the impact of external debt on growth in developing countries. Their general findings though revealing need to be confirmed in Ghana. This paper estimates empirically the impact of external debt on economic growth in Ghana to determine the existence of a ‘debt overhang’ and/or ’crowding out’ effects for the period 1970 to 1999. We used the ADF, PP and KPSS tests for unit roots and the Johansen-Juselius multivariate approach to cointegration to test for stationarity and a long-run relationship among variables. A vector error correction model (VECM) was used to estimate the short-run impacts. The results indicate that GDP growth is influenced positively by external debt inflows and negatively by debt servicing revealing the presence of a ‘crowding out effect’. An indication of a ‘debt overhang effect’ is also found through the negative impact of domestic investment.